y = 7sin^-1(x^2)I got (2x/(sqrt(49-x^4)) but I'm not sure if it is correct. Thank you.
its not correct...the formula for sine inverse is d/dx(sin^-1) = 1/(sqrt(1-x^2))in our equation put u=x^2d/dx(sin^-1(u)) = 7*1/(sqrt(1-u^2)) * du/dx= 7/(sqrt(1-x^4)*2x=14x/(sqrt(1-x^4) (Answer)Please best my answer and add me as your tutor for any further help. Thanks :)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?